Sodium ion battery capable of improving rapid charging performance

By optimizing the positive and negative electrode materials, ceramic separator, and multi-component electrolyte system of sodium-ion batteries, the problem of fast charging of sodium-ion batteries being limited to 0%-80% SOC has been solved, achieving high-rate charging of over 80% and high-frequency cycle stability, making it suitable for scenarios such as food delivery and logistics two-wheeled vehicles.

CN121709694APending Publication Date: 2026-03-20ZHEJIANG HUAYU NADIAN NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610001129.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-04
Publication Date
2026-03-20

AI Technical Summary

Technical Problem

The fast charging performance of existing sodium-ion batteries is limited to the range of 0%-80% battery state of charge. Above 80%, a low-current charging method is required, which cannot meet the needs of high-frequency charging and discharging scenarios, and the cycle stability is poor.

Method used

A specific ratio of positive and negative electrode materials, ceramic membrane, and multi-component electrolyte system is used, including solvents such as methyl ethyl carbonate, propylene carbonate, and diethyl carbonate, and sodium hexafluorophosphate electrolyte. Electrolyte additives such as sodium difluorosulfonamide are added to form a stable SEI membrane, optimize the compatibility of the electrode and membrane interface, inhibit dendrite growth, and improve ion conduction efficiency.

Benefits of technology

Breaking through the limitations of fast charging range, it achieves 2C-3C fast charging in the 0-90% SOC range, improves cycle stability, adapts to high-frequency charging and discharging scenarios, has controllable material costs, and has the potential for large-scale industrialization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121709694A_ABST
    Figure CN121709694A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery capable of improving rapid charging performance, performance breakthrough is realized through common optimization design of multiple components of positive and negative electrode materials, a diaphragm and electrolyte, and the positive electrode material is composed of sodium nickel iron manganese oxide, polyvinylidene fluoride, conductive carbon black and carbon nanotubes; a negative electrode material adopts a hard carbon material matched with a conductive agent and a composite binder, and the binder comprises sodium carboxymethyl cellulose, 3-(5-(2-nitrophenyl)-2-furan) acrylic acid and 4-(hydroxymethyl) phenylboronic acid pinacol ester; the diaphragm is a ceramic coating polyvinyl base membrane, the electrolyte takes sodium hexafluorophosphate as an electrolyte and is matched with an electrolyte additive and a composite solvent, and the electrolyte additive comprises three to five of sodium bis (fluorosulfonyl) imide, sodium difluorophosphate, sodium difluoro (oxalato) borate, ethylene sulfate, fluoroethylene carbonate and ethylene sulfite. The composite solvent comprises methyl ethyl carbonate, propylene carbonate and diethyl carbonate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery technology, and specifically relates to a sodium-ion battery with improved fast charging performance. Background Technology

[0002] Electrochemical energy storage technology is a core support for the construction of new power systems and the green and low-carbon transformation of energy. Guided by the goals of carbon peaking and carbon neutrality, my country has introduced a number of policies to promote the industrialization of new energy storage technologies. Sodium-ion batteries, with their outstanding advantages such as the extremely high abundance of sodium in the Earth's crust, low production costs, and excellent safety, have become one of the core candidate technologies in the field of large-scale electrochemical energy storage, and have broad application prospects in scenarios such as charging piles, frequency regulation services, data centers, and two-wheeled vehicles for food delivery and logistics.

[0003] In practical applications, fast charging performance is a key factor restricting the marketization of sodium-ion batteries, especially in scenarios such as two-wheeled vehicles and emergency power supplies, where the demand for continuous fast charging is extremely urgent. Existing sodium-ion battery fast charging technologies have significant limitations. Their fast charging range is concentrated within the 0%-80% battery state of charge range, which takes 30-45 minutes to complete. Above 80% battery state of charge, a low-current charging mode is required for full charging, failing to meet the efficient continuous fast charging requirements of scenarios such as two-wheeled vehicles. Furthermore, existing technologies lack solutions to overcome the limitations of the fast charging range through multi-component optimization of positive and negative electrode materials, separators, and electrolytes, making it difficult to simultaneously achieve good cycle stability and rate performance of sodium-ion batteries in high-frequency charge-discharge scenarios.

[0004] Therefore, developing a sodium-ion battery that can maintain a high charging rate in the range above 80% battery state of charge is of great significance for promoting the industrialization of sodium-ion batteries and expanding their application scenarios. Summary of the Invention

[0005] The purpose of this invention is to provide a sodium-ion battery that can overcome the limitations of fast charging range, maintain high-rate charging capability above 80% SOC, and have excellent cycle stability, thereby improving fast charging performance. It aims to solve the core pain points of existing sodium-ion batteries, which are limited to fast charging in the 0%-80% SOC range, take a long time to fully charge, and have rapid performance degradation under high-frequency charging and discharging.

[0006] The technical solution adopted by the present invention to achieve the above objectives is as follows: A sodium-ion battery includes an electrolyte comprising a mixed solvent, an electrolyte, and electrolyte additives.

[0007] Preferably, the mixed solvent includes methyl ethyl carbonate, propylene carbonate, and diethyl carbonate.

[0008] Preferably, the electrolyte comprises sodium hexafluorophosphate.

[0009] Preferably, the electrolyte additives include three to five of the following: sodium difluorosulfonylimide, sodium difluorophosphate, sodium difluorooxalate borate, vinyl sulfate, fluoroethylene carbonate, and vinyl sulfite.

[0010] Preferably, the mass-to-volume ratio of electrolyte to mixed solvent is 160-240 g: 1 L.

[0011] Preferably, the mass-to-volume ratio of electrolyte additive to mixed solvent is 3-60 g: 1 L.

[0012] Preferably, in the mixed solvent, the volume ratio of methyl ethyl carbonate to propylene carbonate is 1-2:1-2.

[0013] Preferably, in the mixed solvent, the volume ratio of methyl ethyl carbonate to diethyl carbonate is 1-2:0.1-0.5.

[0014] The composite system of methyl ethyl carbonate, propylene carbonate and diethyl carbonate provides a good dissolution ring for the electrolyte; the electrolyte additives work synergistically to form a low-impedance stable SEI film, effectively inhibiting dendrite growth, and improving the electrolyte ion conduction efficiency, thereby breaking through the fast charging range limitation of sodium-ion batteries, enhancing high-rate charging capability, and improving cycle stability, making it suitable for high-frequency charge and discharge scenarios.

[0015] Preferably, the sodium-ion battery includes a ceramic separator.

[0016] Preferably, the ceramic diaphragm is a polyethylene-based membrane with a boehmite coating.

[0017] Preferably, the thickness of the ceramic diaphragm is 10-15 μm.

[0018] The flexibility of the polyethylene film and the boehmite coating together optimize the interfacial compatibility between the electrode and the separator, inhibit the formation of dendrites by sodium ion deposition, and improve the wettability of the electrolyte to reduce the interfacial impedance during fast charging. It effectively avoids the risk of dendrite puncture, enhances the stability of the battery structure, and works synergistically with the positive and negative electrodes and electrolyte system to further enhance fast charging performance and cycle reliability, making it suitable for high-frequency charge and discharge scenarios.

[0019] Preferably, the sodium-ion battery includes a positive electrode.

[0020] Preferably, the areal density of the positive electrode sheet is 200-280 g / m³. 2 Preferably, the positive electrode sheet includes a positive electrode active material, a positive electrode binder, and a positive electrode conductive agent.

[0021] Preferably, the positive electrode active material includes sodium nickel iron manganese oxide, and the positive electrode binder includes polyvinylidene fluoride.

[0022] Preferably, the mass ratio of the positive electrode active material to the positive electrode binder is 93-96:2-3.

[0023] Preferably, the positive electrode conductive agent includes conductive carbon black and carbon nanotubes.

[0024] Preferably, the mass ratio of the positive electrode active material to the positive electrode conductive agent is 93-96:1-5.

[0025] Preferably, the sodium-ion battery includes a negative electrode.

[0026] Preferably, the areal density of the negative electrode is 100-130 g / m³. 2 .

[0027] Preferably, the negative electrode sheet includes a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder.

[0028] Preferably, the negative electrode active material includes hard carbon material.

[0029] Preferably, the negative electrode conductive agent includes conductive carbon black and carbon nanotubes. Preferably, the mass ratio of the negative electrode active material to the negative electrode conductive agent is 92-96:0.8-2.5.

[0030] Preferably, the negative electrode binder includes sodium carboxymethyl cellulose.

[0031] Preferably, the mass ratio of the negative electrode active material to the negative electrode binder is 92-96:1.5-7.2.

[0032] Preferably, the negative electrode binder comprises 3-(5-(2-nitrophenyl)-2-furan)acrylic acid and 4-(hydroxymethyl)phenylboronic acid pinacol ester.

[0033] Preferably, the mass ratio of sodium carboxymethyl cellulose to 3-(5-(2-nitrophenyl)-2-furan)acrylic acid is 0.6-2:1-2.5.

[0034] Preferably, the mass ratio of sodium carboxymethyl cellulose to pinacol 4-(hydroxymethyl)phenylboronic acid is 0.6-2:1-2.5.

[0035] When 3-(5-(2-nitrophenyl)-2-furan)acrylic acid and 4-(hydroxymethyl)phenylboronic acid pinacol ester are used as a negative electrode composite binder, they form a stable cross-linked network structure, constructing a three-dimensional interwoven polymer skeleton. This effectively buffers the electrode volume expansion caused by the rapid insertion and extraction of sodium ions during fast charging, preventing the active material from loosening and falling off, and ensuring the long-term integrity of the electrode structure. On the other hand, it can optimize the transport environment of sodium ions inside the negative electrode, reduce adsorption and extraction resistance, improve ion migration rate, and enhance the mechanical toughness and conductive network stability of the electrode. This improves the fast charging capability and cycle stability of sodium-ion batteries, enabling the battery to maintain a high capacity retention rate under high-frequency charge and discharge conditions.

[0036] Preferably, the sodium-ion battery cell NP ratio is 1.2-1.25 and the electrolyte injection coefficient is 5.0-5.5 g / Ah.

[0037] The preparation method of the negative electrode in a sodium-ion battery includes, The negative electrode active material, negative electrode conductive agent and negative electrode binder are mixed evenly and stirred at 500-700 rpm for 2-4 hours to obtain the negative electrode slurry. The negative electrode slurry is coated onto a copper foil current collector, dried by blowing at 90-110℃ for 10-15 hours, and then rolled under a pressure of 12-18MPa to obtain the negative electrode sheet.

[0038] Preferably, the negative electrode active material includes hard carbon material.

[0039] Preferably, the negative electrode conductive agent includes conductive carbon black and carbon nanotubes.

[0040] Preferably, the negative electrode binder includes sodium carboxymethyl cellulose, 3-(5-(2-nitrophenyl)-2-furan)acrylic acid and 4-(hydroxymethyl)phenylboronic acid pinacol ester.

[0041] Preferably, the mass ratio of the negative electrode active material to the negative electrode conductive agent is 92-96:0.8-2.5.

[0042] Preferably, the mass ratio of the negative electrode active material to the negative electrode binder is 92-96:1.5-7.2.

[0043] More preferably, the negative electrode binder includes 2-(4-methyl-1H-indole-3-yl)acetic acid, and the mass ratio of sodium carboxymethyl cellulose to 2-(4-methyl-1H-indole-3-yl)acetic acid is 0.6-2:0.4-1.2.

[0044] 2-(4-Methyl-1H-indol-3-yl)acetic acid, as a key functional component of the negative electrode composite binder, can form a dense cross-linked network structure with components such as sodium carboxymethyl cellulose, 3-(5-(2-nitrophenyl)-2-furan)acrylic acid, and 4-(hydroxymethyl)phenylboronic acid pinacol ester through the synergistic effect of functional groups, further improving the three-dimensional interwoven polymer skeleton. It effectively resists the electrode volume deformation caused by sodium ion insertion and extraction during fast charging, avoids the shedding of active material and the breakage of conductive network, and can also optimize the sodium ion transport path by adjusting the internal microenvironment of the electrode, reduce ion migration resistance, and improve the mechanical toughness and chemical stability of the electrode. In this way, it can jointly improve the fast charging capability and long-term cycle performance of sodium-ion batteries, so that the battery can still maintain excellent capacity retention under high-frequency charge and discharge conditions.

[0045] This invention also provides a method for preparing a positive electrode, comprising: The positive electrode active material, positive electrode binder, and positive electrode conductive agent are uniformly mixed and stirred at 700-900 rpm for 1-3 hours to obtain a positive electrode slurry. The positive electrode slurry is coated onto an aluminum foil current collector, vacuum dried at 110-130℃ for 10-15 hours, and rolled under a pressure of 12-18 MPa to obtain a positive electrode sheet.

[0046] Preferably, the positive electrode active material includes sodium nickel iron manganese oxide.

[0047] Preferably, the positive electrode binder includes polyvinylidene fluoride.

[0048] Preferably, the positive electrode conductive agent includes conductive carbon black and carbon nanotubes.

[0049] Preferably, the mass ratio of the positive electrode active material to the positive electrode binder is 93-96:2-3.

[0050] Preferably, the mass ratio of the positive electrode active material to the positive electrode conductive agent is 93-96:1-5.

[0051] Preferably, in the positive electrode conductive agent, the mass ratio of conductive carbon black to carbon nanotubes is 0.7-4:0.3-1.

[0052] This invention also provides a method for preparing a negative electrode, comprising: The negative electrode active material, negative electrode conductive agent and negative electrode binder are uniformly mixed and stirred at 500-700 rpm for 2-4 hours to obtain a negative electrode slurry. The negative electrode slurry is coated on a copper foil current collector, dried in a forced air at 90-110℃ for 10-15 hours, and rolled under a pressure of 12-18 MPa to obtain a negative electrode sheet.

[0053] Preferably, the negative electrode active material includes hard carbon material.

[0054] Preferably, the negative electrode conductive agent includes conductive carbon black and carbon nanotubes.

[0055] Preferably, the negative electrode binder includes sodium carboxymethyl cellulose.

[0056] Preferably, the negative electrode binder includes one or more of styrene-butadiene rubber, polyacrylic acid, 3-(5-(2-nitrophenyl)-2-furan)acrylic acid and 4-(hydroxymethyl)phenylboronic acid pinacol ester.

[0057] Preferably, the mass ratio of the negative electrode active material to the negative electrode conductive agent is 92-96:0.8-2.5.

[0058] Preferably, in the negative electrode conductive agent, the mass ratio of conductive carbon black to carbon nanotubes is 0.5-1.5:0.3-1.

[0059] Preferably, the mass ratio of the negative electrode active material to the negative electrode binder is 92-96:1.5-7.2.

[0060] Preferably, in the negative electrode binder, the mass ratio of sodium carboxymethyl cellulose to styrene-butadiene rubber is 0.6-2:2-4.

[0061] Preferably, in the negative electrode binder, the mass ratio of sodium carboxymethyl cellulose to polyacrylic acid is 0.6-2:0.2-1.5.

[0062] Preferably, in the negative electrode binder, the mass ratio of sodium carboxymethyl cellulose to 3-(5-(2-nitrophenyl)-2-furan)acrylic acid is 0.6-2:1-2.5.

[0063] Preferably, in the negative electrode binder, the mass ratio of sodium carboxymethyl cellulose to pinacol 4-(hydroxymethyl)phenylboronic acid is 0.6-2:1-2.5.

[0064] More preferably, the negative electrode binder includes 2-(4-methyl-1H-indol-3-yl)acetic acid.

[0065] More preferably, in the negative electrode binder, the mass ratio of sodium carboxymethyl cellulose to 2-(4-methyl-1H-indol-3-yl)acetic acid is 0.6-2:0.4-1.2.

[0066] The present invention also provides a method for preparing an electrolyte, comprising: In an argon-protected glove box, the electrolyte is dissolved in a mixed solvent, and sodium difluorosulfonamide, vinyl sulfate, fluoroethylene carbonate and vinyl sulfite are added. The mixture is stirred at 400-600 rpm for 0.5-1.5 h to obtain the electrolyte solution.

[0067] Preferably, the mixed solvent includes methyl ethyl carbonate, propylene carbonate, and diethyl carbonate.

[0068] Preferably, in the mixed solvent, the volume ratio of ethyl methyl carbonate to propylene carbonate is 1-2:1-2.

[0069] Preferably, in the mixed solvent, the volume ratio of methyl ethyl carbonate to diethyl carbonate is 1-2:0.1-0.5.

[0070] Preferably, the electrolyte comprises sodium hexafluorophosphate.

[0071] Preferably, the mass-to-volume ratio of electrolyte to mixed solvent is 160-240 g: 1 L.

[0072] Preferably, the electrolyte additives include three to five of the following: sodium difluorosulfonylimide, sodium difluorophosphate, sodium difluorooxalate borate, vinyl sulfate, fluoroethylene carbonate, and vinyl sulfite.

[0073] Preferably, the mass-to-volume ratio of electrolyte additive to mixed solvent is 3-60 g: 1 L.

[0074] More preferably, the mass-to-volume ratio of sodium difluorosulfonamide to the mixed solvent is 1-20 g: 1 L.

[0075] More preferably, the mass-to-volume ratio of sodium difluorophosphate to the mixed solvent is 1-10 g:1 L.

[0076] More preferably, the mass-to-volume ratio of sodium difluorooxalate borate to the mixed solvent is 1-15 g: 1 L.

[0077] More preferably, the mass-to-volume ratio of vinyl sulfate to the mixed solvent is 5-20 g: 1 L.

[0078] More preferably, the mass-to-volume ratio of fluoroethylene carbonate to the mixed solvent is 5-10 g:1 L.

[0079] More preferably, the mass-to-volume ratio of vinyl sulfite to the mixed solvent is 5-10 g:1 L.

[0080] This invention also provides a method for preparing a sodium-ion battery, comprising: A sodium-ion battery is obtained by stacking positive electrode plates, ceramic separators and negative electrode plates in sequence using a stacked structure, packing them into an aluminum-plastic film package, injecting electrolyte, and then vacuum sealing and static activation.

[0081] Preferably, the ceramic diaphragm is a polyethylene-based membrane with a boehmite coating and a thickness of 10-15 μm.

[0082] Preferably, the areal density of the positive electrode sheet is 200-280 g / m³. 2 .

[0083] Preferably, the areal density of the negative electrode is 100-130 g / m³. 2.

[0084] Preferably, the NP ratio of the core is 1.2-1.25.

[0085] Preferably, the injection coefficient is 5-5.5 g / Ah.

[0086] This invention utilizes a specific ratio of positive and negative electrode materials, a ceramic separator, and a multi-component optimized electrolyte system. The positive and negative electrode materials improve ion conduction efficiency through a specific ratio of active materials, conductive agents, and binders. The electrolyte uses sodium hexafluorophosphate as the electrolyte, and 3-5 electrolyte additives and composite solvents are added to form a stable SEI film and inhibit dendrite growth. Simultaneously, the NP ratio and electrolyte injection coefficient of the cell are optimized. Therefore, this invention offers the following advantages: it successfully overcomes the limitations of existing sodium-ion batteries in the fast-charging range, achieving 2C-3C fast charging within the 0-90% SOC range; it significantly improves cycle stability, making it suitable for high-frequency usage scenarios such as delivery and logistics two-wheeled vehicles; and it features controllable material costs and a mature manufacturing process, possessing the potential for large-scale industrialization. Therefore, this invention is a sodium-ion battery with outstanding fast-charging performance, reliable cycle stability, and suitability for high-frequency charging and discharging scenarios, improving fast-charging performance. Attached Figure Description

[0087] Figure 1 This is a schematic diagram showing the 3C fast charging performance test results of the sodium-ion battery prepared in Example 1.

[0088] Figure 2 This is a schematic diagram of the 2C fast charging performance test results of the sodium-ion battery prepared in Example 1.

[0089] Figure 3 This is a schematic diagram showing the charge-discharge cycle results of the sodium-ion battery prepared in Example 1. Detailed Implementation

[0090] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0091] The concepts involved in this application will first be described with reference to the accompanying drawings. It should be noted that the following descriptions of various concepts are only for the purpose of making the content of this application easier to understand and do not constitute a limitation on the scope of protection of this application; furthermore, the embodiments and features in the embodiments of this application can be combined with each other unless otherwise specified. This application will now be described in detail with reference to the accompanying drawings and embodiments.

[0092] Example 1: Preparation of the positive electrode sheet: Sodium nickel iron manganese oxide, polyvinylidene fluoride, conductive carbon black, and carbon nanotubes were uniformly mixed and stirred at 800 rpm for 2 hours to obtain a positive electrode slurry. The positive electrode slurry was coated onto an aluminum foil current collector, vacuum dried at 120℃ for 12 hours, and then rolled under 15 MPa pressure to obtain the positive electrode sheet. The mass ratio of sodium nickel iron manganese oxide to polyvinylidene fluoride was 94:2.5, the mass ratio of sodium nickel iron manganese oxide to conductive carbon black was 94:3, and the mass ratio of sodium nickel iron manganese oxide to carbon nanotubes was 94:0.5.

[0093] Preparation of the negative electrode sheet: Hard carbon material, conductive carbon black, carbon nanotubes, sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyacrylic acid were uniformly mixed and stirred at 600 rpm for 3 hours to obtain a negative electrode slurry. The negative electrode slurry was coated onto a copper foil current collector and dried in a forced-air environment at 100°C for 12 hours. The negative electrode sheet was then rolled under a pressure of 15 MPa. The mass ratio of hard carbon material to conductive carbon black was 94.5:1, the mass ratio of hard carbon material to carbon nanotubes was 94.5:0.4, the mass ratio of hard carbon material to sodium carboxymethyl cellulose was 94.5:0.9, the mass ratio of hard carbon material to styrene-butadiene rubber was 94.5:2.5, and the mass ratio of hard carbon material to polyacrylic acid was 94.5:0.7.

[0094] Preparation of electrolyte: In an argon-protected glove box, methyl ethyl carbonate, propylene carbonate, and diethyl carbonate were uniformly mixed to obtain a mixed solvent. Sodium hexafluorophosphate was dissolved in the mixed solvent, and sodium bis(fluorosulfonyl)imide, vinyl sulfate, fluoroethylene carbonate, and vinyl sulfite were added. The mixture was stirred at 500 rpm for 1 h to obtain the electrolyte. In the mixed solvent, the volume ratio of methyl ethyl carbonate to propylene carbonate was 1:1, and the volume ratio of methyl ethyl carbonate to diethyl carbonate was 1:0.2. The mass-to-volume ratio of sodium hexafluorophosphate to the mixed solvent was 184.8 g:1 L, the mass-to-volume ratio of sodium bis(fluorosulfonyl)imide to the mixed solvent was 10 g:1 L, the mass-to-volume ratio of vinyl sulfate to the mixed solvent was 10 g:1 L, the mass-to-volume ratio of fluoroethylene carbonate to the mixed solvent was 5 g:1 L, and the mass-to-volume ratio of vinyl sulfite to the mixed solvent was 5 g:1 L.

[0095] Sodium-ion battery fabrication: A stacked structure is used, in which the positive electrode, ceramic separator, and negative electrode are sequentially stacked, packaged in an aluminum-plastic film, injected with electrolyte, and then vacuum-sealed and activated to obtain the sodium-ion battery. The ceramic separator is a polyethylene-based film with a boehmite coating, with a thickness of 12 μm; the areal density of the positive electrode is 240 g / m³. 2 The surface density of the negative electrode is 115 g / m³. 2 The cell has an NP ratio of 1.23 and an electrolyte injection coefficient of 5.35 g / Ah.

[0096] Example 2: The only difference between this example and Example 1 is the preparation of the electrolyte.

[0097] Electrolyte preparation: In an argon-protected glove box, methyl ethyl carbonate, propylene carbonate, and diethyl carbonate were uniformly mixed to obtain a mixed solvent. Sodium hexafluorophosphate was dissolved in the mixed solvent, and sodium difluorosulfonyl imide, sodium difluorophosphate, vinyl sulfate, and fluoroethylene carbonate were added. The mixture was stirred at 500 rpm for 1 h to obtain the electrolyte. In the mixed solvent, the volume ratio of methyl ethyl carbonate to propylene carbonate was 3:2, and the volume ratio of methyl ethyl carbonate to diethyl carbonate was 6:1. The mass-volume ratio of sodium hexafluorophosphate to the mixed solvent was 201.6 g:1 L, the mass-volume ratio of sodium difluorosulfonyl imide to the mixed solvent was 7.2 g:1 L, the mass-volume ratio of sodium difluorophosphate to the mixed solvent was 4.5 g:1 L, the mass-volume ratio of vinyl sulfate to the mixed solvent was 10.8 g:1 L, and the mass-volume ratio of fluoroethylene carbonate to the mixed solvent was 7.2 g:1 L.

[0098] Example 3: The only difference between this example and Example 1 is the preparation of the electrolyte.

[0099] Preparation of electrolyte: In an argon-protected glove box, methyl ethyl carbonate, propylene carbonate and diethyl carbonate were uniformly mixed to obtain a mixed solvent; sodium hexafluorophosphate was dissolved in the mixed solvent, and sodium difluorosulfonamide, sodium difluorophosphate, sodium difluorooxalate borate, vinyl sulfate and vinyl sulfite were added. The mixture was stirred at 500 rpm for 1 h to obtain the electrolyte. In the mixed solvent, the volume ratio of methyl ethyl carbonate to propylene carbonate is 1:1, and the volume ratio of methyl ethyl carbonate to diethyl carbonate is 5:1; the mass-volume ratio of sodium hexafluorophosphate to the mixed solvent is 168 g:1 L, the mass-volume ratio of sodium difluorosulfonyl imide to the mixed solvent is 4.5 g:1 L, the mass-volume ratio of sodium difluorophosphate to the mixed solvent is 2.7 g:1 L, the mass-volume ratio of sodium difluorooxalate borate to the mixed solvent is 7.2 g:1 L, the mass-volume ratio of vinyl sulfate to the mixed solvent is 13.5 g:1 L, and the mass-volume ratio of vinyl sulfite to the mixed solvent is 6.3 g:1 L.

[0100] Example 4: The only difference between this example and Example 1 is the preparation of the negative electrode.

[0101] Preparation of the negative electrode: Hard carbon material, conductive carbon black, carbon nanotubes, sodium carboxymethyl cellulose, 3-(5-(2-nitrophenyl)-2-furan)acrylic acid, and pinacol ester of 4-(hydroxymethyl)phenylboronic acid were uniformly mixed and stirred at 600 rpm for 3 h to obtain a negative electrode slurry. The negative electrode slurry was coated onto a copper foil current collector and dried in a forced-air environment at 100℃ for 12 h. The negative electrode was then rolled under a pressure of 15 MPa to obtain the negative electrode sheet. The mass ratio of hard carbon material to conductive carbon black was 94.5:1, the mass ratio of hard carbon material to carbon nanotubes was 94.5:0.4, the mass ratio of hard carbon material to sodium carboxymethyl cellulose was 94.5:0.9, the mass ratio of hard carbon material to 3-(5-(2-nitrophenyl)-2-furan)acrylic acid was 94.5:1.1, and the mass ratio of hard carbon material to pinacol ester of 4-(hydroxymethyl)phenylboronic acid was 94.5:1.6.

[0102] Example 5: The only difference between this example and Example 1 is the preparation of the negative electrode.

[0103] Preparation of the negative electrode: Hard carbon material, conductive carbon black, carbon nanotubes, sodium carboxymethyl cellulose, 3-(5-(2-nitrophenyl)-2-furan)acrylic acid, and pinacol ester of 4-(hydroxymethyl)phenylboronic acid were uniformly mixed and stirred at 600 rpm for 3 h to obtain a negative electrode slurry. The negative electrode slurry was coated onto a copper foil current collector and dried in a forced-air environment at 100℃ for 12 h. The negative electrode was then rolled under a pressure of 15 MPa to obtain the negative electrode sheet. The mass ratio of hard carbon material to conductive carbon black was 94.5:1, the mass ratio of hard carbon material to carbon nanotubes was 94.5:0.4, the mass ratio of hard carbon material to sodium carboxymethyl cellulose was 94.5:0.9, the mass ratio of hard carbon material to 3-(5-(2-nitrophenyl)-2-furan)acrylic acid was 94.5:1.6, and the mass ratio of hard carbon material to pinacol ester of 4-(hydroxymethyl)phenylboronic acid was 94.5:1.6.

[0104] Example 6: The only difference between this example and Example 1 is the preparation of the negative electrode.

[0105] Preparation of negative electrode sheet: Hard carbon material, conductive carbon black, carbon nanotubes, sodium carboxymethyl cellulose, 3-(5-(2-nitrophenyl)-2-furan)acrylic acid, pinacol ester of 4-(hydroxymethyl)phenylboronic acid, and 2-(4-methyl-1H-indol-3-yl)acetic acid are uniformly mixed and stirred at 600 rpm for 3 h to obtain negative electrode slurry; the negative electrode slurry is coated on copper foil current collector, dried in a forced air at 100℃ for 12 h, and rolled under 15 MPa pressure to obtain negative electrode sheet. The mass ratio of hard carbon material to conductive carbon black is 94.5:1, the mass ratio of hard carbon material to carbon nanotubes is 94.5:0.4, the mass ratio of hard carbon material to sodium carboxymethyl cellulose is 94.5:0.9, the mass ratio of hard carbon material to 3-(5-(2-nitrophenyl)-2-furan)acrylic acid is 94.5:1.1, the mass ratio of hard carbon material to pinacol 4-(hydroxymethyl)phenylboronic acid is 94.5:1.6, and the mass ratio of hard carbon material to 2-(4-methyl-1H-indol-3-yl)acetic acid is 94.5:0.5.

[0106] Example 7: The only difference between this example and Example 1 is the preparation of the negative electrode.

[0107] Preparation of negative electrode sheet: Hard carbon material, conductive carbon black, carbon nanotubes, sodium carboxymethyl cellulose, 3-(5-(2-nitrophenyl)-2-furan)acrylic acid, pinacol ester of 4-(hydroxymethyl)phenylboronic acid, and 2-(4-methyl-1H-indol-3-yl)acetic acid are uniformly mixed and stirred at 600 rpm for 3 h to obtain negative electrode slurry; the negative electrode slurry is coated on copper foil current collector, dried in a forced air at 100℃ for 12 h, and rolled under 15 MPa pressure to obtain negative electrode sheet. The mass ratio of hard carbon material to conductive carbon black is 94.5:1, the mass ratio of hard carbon material to carbon nanotubes is 94.5:0.4, the mass ratio of hard carbon material to sodium carboxymethyl cellulose is 94.5:0.9, the mass ratio of hard carbon material to 3-(5-(2-nitrophenyl)-2-furan)acrylic acid is 94.5:1.1, the mass ratio of hard carbon material to pinacol 4-(hydroxymethyl)phenylboronic acid is 94.5:1.6, and the mass ratio of hard carbon material to 2-(4-methyl-1H-indol-3-yl)acetic acid is 94.5:1.

[0108] Comparative Example 1: The only difference between this comparative example and Example 1 is the preparation of the electrolyte.

[0109] Electrolyte preparation: In an argon-protected glove box, methyl ethyl carbonate, propylene carbonate, and diethyl carbonate were uniformly mixed to obtain a mixed solvent. Sodium hexafluorophosphate was dissolved in the mixed solvent, and fluoroethylene carbonate was added. The mixture was stirred at 500 rpm for 1 h to obtain the electrolyte. In the mixed solvent, the volume ratio of methyl ethyl carbonate to propylene carbonate was 1:1, and the volume ratio of methyl ethyl carbonate to diethyl carbonate was 1:0.2. The mass-to-volume ratio of sodium hexafluorophosphate to the mixed solvent was 184.8 g:1 L, and the mass-to-volume ratio of fluoroethylene carbonate to the mixed solvent was 4.5 g:1 L.

[0110] Comparative Example 2: The only difference between this comparative example and Example 1 is the preparation of the electrolyte.

[0111] Preparation of electrolyte: In an argon-protected glove box, methyl ethyl carbonate and propylene carbonate were uniformly mixed to obtain a mixed solvent. Sodium hexafluorophosphate was dissolved in the mixed solvent, and sodium difluorosulfonyl imide, vinyl sulfate, fluoroethylene carbonate, and vinyl sulfite were added. The mixture was stirred at 500 rpm for 1 h to obtain the electrolyte. In the mixed solvent, the volume ratio of methyl ethyl carbonate to propylene carbonate was 1:1; the mass-to-volume ratio of sodium hexafluorophosphate to the mixed solvent was 184.8 g:1 L; the mass-to-volume ratio of sodium difluorosulfonyl imide to the mixed solvent was 9 g:1 L; the mass-to-volume ratio of vinyl sulfate to the mixed solvent was 9 g:1 L; the mass-to-volume ratio of fluoroethylene carbonate to the mixed solvent was 4.5 g:1 L; and the mass-to-volume ratio of vinyl sulfite to the mixed solvent was 4.5 g:1 L.

[0112] Comparative Example 3: The only difference between this comparative example and Example 1 is the preparation of the electrolyte.

[0113] Electrolyte preparation: In an argon-protected glove box, methyl ethyl carbonate and propylene carbonate were uniformly mixed to obtain a mixed solvent. Sodium hexafluorophosphate was dissolved in the mixed solvent, and fluoroethylene carbonate was added. The mixture was stirred at 500 rpm for 1 h to obtain the electrolyte. In the mixed solvent, the volume ratio of methyl ethyl carbonate to propylene carbonate was 1:1; the mass-to-volume ratio of sodium hexafluorophosphate to the mixed solvent was 184.8 g:1 L; and the mass-to-volume ratio of fluoroethylene carbonate to the mixed solvent was 4.5 g:1 L.

[0114] Comparative Example 4: The only difference between this comparative example and Example 1 is the preparation of the negative electrode.

[0115] Preparation of the negative electrode: Hard carbon material, conductive carbon black, carbon nanotubes, sodium carboxymethyl cellulose, and 3-(5-(2-nitrophenyl)-2-furan)acrylic acid were uniformly mixed and stirred at 600 rpm for 3 h to obtain a negative electrode slurry. The negative electrode slurry was coated onto a copper foil current collector and dried in a forced-air environment at 100℃ for 12 h. The negative electrode was then rolled under a pressure of 15 MPa to obtain the negative electrode sheet. The mass ratio of hard carbon material to conductive carbon black was 94.5:1, the mass ratio of hard carbon material to carbon nanotubes was 94.5:0.4, the mass ratio of hard carbon material to sodium carboxymethyl cellulose was 94.5:0.9, and the mass ratio of hard carbon material to 3-(5-(2-nitrophenyl)-2-furan)acrylic acid was 94.5:1.1.

[0116] Comparative Example 5: The only difference between this comparative example and Example 1 is the preparation of the negative electrode.

[0117] Preparation of the negative electrode: Hard carbon material, conductive carbon black, carbon nanotubes, sodium carboxymethyl cellulose, and pinacol ester of 4-(hydroxymethyl)phenylboronic acid were uniformly mixed and stirred at 600 rpm for 3 hours to obtain a negative electrode slurry. The negative electrode slurry was coated onto a copper foil current collector and dried in a forced-air environment at 100℃ for 12 hours. The negative electrode was then rolled under a pressure of 15 MPa to obtain the negative electrode sheet. The mass ratio of hard carbon material to conductive carbon black was 94.5:1, the mass ratio of hard carbon material to carbon nanotubes was 94.5:0.4, the mass ratio of hard carbon material to sodium carboxymethyl cellulose was 94.5:0.9, and the mass ratio of hard carbon material to pinacol ester of 4-(hydroxymethyl)phenylboronic acid was 94.5:1.6.

[0118] Comparative Example 6: The only difference between this comparative example and Example 1 is the preparation of the negative electrode.

[0119] Preparation of the negative electrode: Hard carbon material, conductive carbon black, carbon nanotubes, and sodium carboxymethyl cellulose were uniformly mixed and stirred at 600 rpm for 3 hours to obtain a negative electrode slurry. The negative electrode slurry was coated onto a copper foil current collector and dried in a forced-air environment at 100℃ for 12 hours. The negative electrode was then rolled under a pressure of 15 MPa to obtain the negative electrode sheet. The mass ratio of hard carbon material to conductive carbon black was 94.5:1, the mass ratio of hard carbon material to carbon nanotubes was 94.5:0.4, and the mass ratio of hard carbon material to sodium carboxymethyl cellulose was 94.5:0.9.

[0120] Test Example 1: Fast charging time test of sodium-ion batteries.

[0121] Test samples: Sodium-ion batteries prepared in each embodiment and comparative example.

[0122] Test method: The charging performance of each battery was tested using a battery testing system. First, the battery was charged from 0% SOC to 85% SOC with a constant current of 3C, and the total charging time of the process was recorded. Then, the battery was charged to 100% SOC with a constant current of 0.5C and discharged to 0% SOC with a constant current of 1C. The charge-discharge cycle was performed, and the discharge capacity of each cycle was recorded and the capacity retention rate was calculated. The test environment temperature was maintained at 25℃.

[0123] The 3C fast charging performance test results of the sodium-ion battery prepared in Example 1 of this invention are as follows: Figure 1 As shown in Table 1, the test results of the 3C fast charging time of the sodium-ion battery prepared by the present invention are as follows.

[0124] Table 1. Test results of 3C fast charging time for sodium-ion batteries

[0125] Examples 1 to 3, through the configuration of the electrolyte system, use sodium hexafluorophosphate as the core electrolyte, combined with sodium difluorosulfonyl imide, vinyl sulfate, fluoroethylene carbonate, vinyl sulfite, sodium difluorophosphate, and sodium difluorooxalate borate as electrolyte additives with multiple components working together. At the same time, methyl ethyl carbonate, propylene carbonate, and diethyl carbonate are selected in a specific ratio to form a mixed solvent. The combined effect of multiple electrolyte additives and composite solvents not only successfully constructs a stable SEI film with low impedance, reducing the resistance in the charge transport process, but also significantly improves the ion conduction efficiency of the electrolyte, allowing sodium ion migration to be smoother, thereby promoting a significant shortening of the fast charging time. Examples 4 and 5 improved the negative electrode binder by introducing 3-(5-(2-nitrophenyl)-2-furan)acrylic acid and 4-(hydroxymethyl)phenylboronic acid pinacol ester. Examples 6 and 7 further introduced 2-(4-methyl-1H-indol-3-yl)acetic acid to form a composite binder system. This composite binder not only enhanced the stability of the electrode structure through strong adhesion, preventing the active material from loosening during charging, but also optimized the adsorption and deintercalation kinetics of sodium ions inside the negative electrode through the synergistic effect of the components, accelerating the migration rate of sodium ions and further shortening the fast charging time. Moreover, with the optimization of the proportion of each component in the composite binder, the charging efficiency showed a progressive improvement trend, fully demonstrating the positive role of the improved negative electrode binder in promoting fast charging performance. Comparative Example 1 uses only fluoroethylene carbonate as a single additive in the electrolyte, lacking the synergistic effect of other components. This makes it difficult to form a stable and low-impedance SEI film, resulting in high charge transport resistance and a significantly prolonged charging time. Comparative Example 2's electrolyte mixture lacks diethyl carbonate, disrupting the synergistic effect of the mixed solvent and leading to insufficient ion conduction rate and a corresponding increase in charging time. Comparative Example 3's electrolyte lacks both diethyl carbonate and only contains the single additive fluoroethylene carbonate. The combined effect of these two defects significantly reduces both ion conduction efficiency and SEI film stability, further prolonging the charging time. Comparative Example 4 uses only 3-(5-(2-nitrophenyl)-2-furan)acrylic acid as a single binder, Comparative Example 5 uses only 4-(hydroxymethyl)phenylboronic acid pinacol ester as a single binder, and Comparative Example 6 uses the traditional sodium carboxymethyl cellulose as a single binder. None of these three methods can achieve the combined optimization of sodium ion transport efficiency and electrode structure stability, making them unsuitable for the requirements of fast charging. Therefore, their charging times are significantly longer than those of the corresponding examples.

[0126] Test Example 2: Fast charging capacity retention test of sodium-ion batteries.

[0127] Test samples: Sodium-ion batteries prepared in each embodiment and comparative example.

[0128] Test method: A battery testing system was used to charge the battery with a constant current of 2C, with a charging range of 0%-85% SOC. Then, the charging was switched to 0.5C to 100% SOC, and then discharged at 1C to 0% SOC. The charge-discharge cycle was performed, and the discharge capacity of each cycle was recorded. The capacity retention rate after 1000 cycles was calculated. The test environment temperature was 25℃.

[0129] The 2C fast charging performance test results of the sodium-ion battery prepared in Example 1 of this invention are as follows: Figure 2 As shown in Table 2, the capacity retention rate test results of the sodium-ion battery prepared by this invention after 2C fast charging are shown in Table 2.

[0130] Table 2. Test results of capacity retention rate of sodium-ion batteries during 2C fast charging.

[0131] Examples 1 to 3 utilize a specific electrolyte system with sodium hexafluorophosphate as the core electrolyte, combined with various additives such as sodium difluorosulfonyl imide and vinyl sulfate. The mixed solvent is composed of methyl ethyl carbonate, propylene carbonate, and diethyl carbonate in precise proportions. Under fast charging conditions, this electrolyte system forms a stable and dense SEI film, effectively inhibiting dendrite growth and electrolyte decomposition, reducing the rapid increase in interfacial impedance during fast charging, and maintaining a high electrolyte ion conduction efficiency. This avoids the structural damage to active materials and rapid capacity decay caused by high-rate charging, resulting in excellent capacity retention after 1000 cycles. Examples 4 to 7 introduce 3-(5-(2-nitrophenyl)-2-furan)acrylic acid, 4-(hydroxymethyl)phenylboronic acid pinacol ester, and 2-(4-methyl-1H-indole-3- The composite binder system composed of ethyl acetate (-ethyl) can tightly encapsulate the negative electrode active materials such as hard carbon materials and conductive carbon black, as well as the conductive agent, through the combined action of its components. This effectively buffers the electrode volume expansion caused by the rapid insertion and extraction of sodium ions during fast charging, continuously maintaining the integrity of the electrode structure and the stability of the conductive network. It avoids the shedding of active materials and deterioration of interface contact, reducing the causes of capacity decay and further improving the capacity retention rate compared to Examples 1 to 3. The example with optimized proportions of the composite binder components exhibits even better cycle stability. In Comparative Example 1, the electrolyte only added fluoroethylene carbonate as a single additive, resulting in an unstable SEI film structure that is prone to rupture and reconstruction during fast charging cycles, leading to a continuous increase in electrode interface impedance and a faster capacity decay rate. In Comparative Example 2, the electrolyte mixed solvent lacked diethyl carbonate, which not only affected the ion conduction efficiency of the electrolyte but also reduced its cycle stability, causing a significant performance decline in the electrode after multiple fast charging cycles, and a corresponding decrease in capacity retention. In Comparative Example 3, the electrolyte lacked both diethyl carbonate and only added fluoroethylene carbonate as a single additive. Vinyl acetate, with its dual defects, resulted in insufficient SEI film stability and electrolyte conductivity, exhibiting the worst capacity retention under fast charging cycles. Comparative Example 4 used only 3-(5-(2-nitrophenyl)-2-furan) acrylic acid as a single binder, Comparative Example 5 used only 4-(hydroxymethyl)phenylboronic acid pinacol ester as a single binder, and Comparative Example 6 used the traditional sodium carboxymethyl cellulose binder. None of these three binders could effectively alleviate electrode volume changes and active material shedding during fast charging, making it difficult to maintain electrode structural integrity, and their capacity retention rates were significantly lower than those of the corresponding examples.

[0132] Test Example 3: Cyclic stability test of sodium-ion batteries.

[0133] Test samples: Sodium-ion batteries prepared in each embodiment and comparative example.

[0134] Test method: A battery test system was used, with the charging regime set to 2C current to charge to 90% SOC and the discharging regime set to 1C current to discharge to 20% SOC. The number of cycles was set to 2400. The discharge capacity of each cycle was recorded and the capacity retention rate was calculated. The test environment temperature was 25℃. After every 50 cycles, the battery was left to stand for 1 hour to eliminate the polarization effect.

[0135] The charge-discharge cycle results of the sodium-ion battery prepared in Example 1 of this invention are as follows: Figure 3 As shown in Table 3, the cycle stability test results of the sodium-ion battery prepared by this invention are as follows.

[0136] Table 3. Cycle stability test results of sodium-ion batteries

[0137] Examples 1 to 3 utilize a specifically optimized electrolyte system, with sodium hexafluorophosphate as the electrolyte core, combined with various additives such as sodium difluorosulfonyl imide and vinyl sulfate, and the mixed solvent includes methyl ethyl carbonate, propylene carbonate, and diethyl carbonate, precisely proportioned. Under long-term high-frequency fast-charge cycling conditions, this electrolyte system can continuously maintain the stability and dense structure of the SEI film, effectively inhibiting dendrite growth and electrolyte decomposition, reducing the cumulative increase of interfacial impedance, and ensuring the ion conduction efficiency of the electrolyte after long-term cycling, avoiding capacity reduction due to electrolyte performance degradation, and maintaining a high capacity retention rate after 2400 cycles. Examples 4 to 7, based on the above electrolyte optimization, use a composite adhesive composed of 3-(5-(2-nitrophenyl)-2-furan)acrylic acid, 4-(hydroxymethyl)phenylboronic acid pinacol ester, and 2-(4-methyl-1H-indole-3-yl)acetic acid. The binder system, through the combined action of its components, tightly encapsulates the anode components such as hard carbon materials, conductive carbon black, and carbon nanotubes. It effectively buffers the electrode volume expansion caused by the rapid insertion and extraction of sodium ions during long-term fast-charging cycles, continuously maintaining the integrity of the electrode structure and the stability of the conductive network. This avoids the problems of active material shedding and deterioration of interfacial contact under long-term cycling, reducing the key factors that cause capacity decay. As a result, the cycle stability is further improved compared to Examples 1 to 3. Moreover, with the optimization of the composite binder component ratio, the long-term cycle capacity retention rate shows a progressively increasing trend, highlighting the important significance of optimizing the composite binder ratio for long-term cycle performance. The electrolyte in Comparative Example 1, with only fluoroethylene carbonate as a single additive, resulted in an SEI film that was prone to rupture and reconstruction during long-term fast-charge cycles, leading to continuous damage to the electrode interface and a sustained rapid capacity decay. The electrolyte in Comparative Example 2, lacking diethyl carbonate in its mixed solvent, not only reduced the electrolyte's ion conduction efficiency but also affected its long-term cycle stability, causing a significant performance decline after multiple cycles and consequently dragging down the battery's cycle performance and capacity retention. The electrolyte in Comparative Example 3 suffered from both the lack of diethyl carbonate and the single additive deficiency. The SEI film stability and electrolyte conductivity could not meet the requirements of long-term fast charging, and the performance under long-term cycling was the worst. Comparative Example 4 used only 3-(5-(2-nitrophenyl)-2-furan) acrylic acid as a single binder, Comparative Example 5 used only 4-(hydroxymethyl)phenylboronic acid pinacol ester as a single binder, and Comparative Example 6 used the traditional sodium carboxymethyl cellulose binder. None of the three could effectively alleviate the changes in electrode volume and the shedding of active material caused by long-term high-frequency fast charging. The integrity of the electrode structure was gradually lost, the conductive network was destroyed, and the cycle stability was significantly weaker than that of the examples.

[0138] The embodiments and / or implementation methods described above are merely preferred embodiments and / or implementation methods for implementing the technology of the present invention, and are not intended to limit the implementation methods of the technology of the present invention in any way. Any person skilled in the art can make some modifications or alterations to other equivalent embodiments without departing from the scope of the technical means disclosed in the content of the present invention, but they should still be regarded as the technology or embodiments that are substantially the same as the present invention.

[0139] This document uses specific examples to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the methods and core ideas of this application. The above descriptions are only preferred embodiments of this application. It should be noted that due to the limitations of written expression, while there are objectively infinite specific structures, those skilled in the art can make several improvements, modifications, or changes without departing from the principles of this application, and can also combine the above technical features in an appropriate manner. These improvements, modifications, changes, or combinations, or the direct application of the inventive concept and technical solution to other situations without modification, should all be considered within the scope of protection of this application.

Claims

1. A sodium-ion battery, characterized in that: The sodium-ion battery includes an electrolyte, which comprises a mixed solvent, an electrolyte, and an electrolyte additive. The mixed solvent includes methyl ethyl carbonate, propylene carbonate, and diethyl carbonate. The electrolyte includes sodium hexafluorophosphate. The electrolyte additive includes three to five of the following: sodium difluorosulfonamide, sodium difluorophosphate, sodium difluorooxalate borate, vinyl sulfate, fluoroethylene carbonate, and vinyl sulfite. The mass-to-volume ratio of the electrolyte to the mixed solvent is 160-240 g:1 L, and the mass-to-volume ratio of the electrolyte additive to the mixed solvent is 3-60 g:1 L.

2. A sodium-ion battery according to claim 1, characterized in that: In the mixed solvent, the volume ratio of methyl ethyl carbonate to propylene carbonate is 1-2:1-2, and the volume ratio of methyl ethyl carbonate to diethyl carbonate is 1-2:0.1-0.

5.

3. A sodium-ion battery according to claim 1, characterized in that: The sodium-ion battery includes a ceramic separator, which is a polyethylene-based membrane with a boehmite coating, and the thickness of the ceramic separator is 10-15 μm.

4. A sodium-ion battery according to claim 1, characterized in that: The sodium-ion battery includes a positive electrode sheet, the positive electrode sheet having an areal density of 200-280 g / m³. 2 The positive electrode sheet includes a positive electrode active material, a positive electrode binder, and a positive electrode conductive agent. The positive electrode active material includes sodium nickel iron manganese oxide, and the positive electrode binder includes polyvinylidene fluoride. The mass ratio of the positive electrode active material to the positive electrode binder is 93-96:2-3.

5. A sodium-ion battery according to claim 4, characterized in that: The positive electrode conductive agent includes conductive carbon black and carbon nanotubes, and the mass ratio of the positive electrode active material to the positive electrode conductive agent is 93-96:1-5.

6. A sodium-ion battery according to claim 1, characterized in that: The sodium-ion battery includes a negative electrode sheet with an areal density of 100-130 g / m³. 2 The negative electrode sheet includes a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder. The negative electrode active material includes hard carbon material, and the negative electrode conductive agent includes conductive carbon black and carbon nanotubes. The mass ratio of the negative electrode active material to the negative electrode conductive agent is 92-96:0.8-2.

5.

7. A sodium-ion battery according to claim 6, characterized in that: The negative electrode binder includes sodium carboxymethyl cellulose, and the mass ratio of the negative electrode active material to the negative electrode binder is 92-96:1.5-7.

2.

8. A sodium-ion battery according to claim 7, characterized in that: The negative electrode binder comprises 3-(5-(2-nitrophenyl)-2-furan)acrylic acid and 4-(hydroxymethyl)phenylboronic acid pinacol ester, wherein the mass ratio of sodium carboxymethyl cellulose to 3-(5-(2-nitrophenyl)-2-furan)acrylic acid is 0.6-2:1-2.5, and the mass ratio of sodium carboxymethyl cellulose to 4-(hydroxymethyl)phenylboronic acid pinacol ester is 0.6-2:1-2.

5.

9. A sodium-ion battery according to claim 1, characterized in that: The sodium-ion battery has a cell NP ratio of 1.2-1.25 and an electrolyte injection coefficient of 5.0-5.5 g / Ah.

10. A method for preparing the negative electrode sheet in a sodium-ion battery according to any one of claims 6-8, characterized in that: include, The negative electrode active material, negative electrode conductive agent and negative electrode binder are mixed evenly and stirred at 500-700 rpm for 2-4 hours to obtain the negative electrode slurry. The negative electrode slurry is coated onto a copper foil current collector, dried in a forced-air dryer at 90-110℃ for 10-15 hours, and then rolled under a pressure of 12-18MPa to obtain the negative electrode sheet. The negative electrode active material includes hard carbon material, the negative electrode conductive agent includes conductive carbon black and carbon nanotubes, and the negative electrode binder includes sodium carboxymethyl cellulose, 3-(5-(2-nitrophenyl)-2-furan)acrylic acid and 4-(hydroxymethyl)phenylboronic acid pinacol ester; The mass ratio of the negative electrode active material to the negative electrode conductive agent is 92-96:0.8-2.5, and the mass ratio of the negative electrode active material to the negative electrode binder is 92-96:1.5-7.2.